Design of a Fixed Wing Martian Aerial Vehicle and Low Reynolds Number Airfoil Analysis ​ - ​​Apostolakopoulos​, Yannis (Cranfield University, 2025)
​​The objective of this thesis is to evaluate the feasibility of a fixed-wing, VTOL capable aircraft for use in the Martian atmosphere which would address a gap in low Reynolds number research for Martian flight. This project is supposed to take over from the limitation NASA’s Ingenuity rotorcraft experienced, promising longer range and higher efficiency. The Martian Aerial Exploration Validation Experiment (MAEVE) is a proposed compact 5kg demonstration platform due to operate in the densest part of the Martian atmosphere (Hellas Basin) to bridge the gap between simple rotorcraft and the future of planetary aerial exploration. This research uses a combination of accurate Martian atmospheric data from the Mars Climate Database v6.1 (Forget, et al., n.d.) and an airfoil analysis tool (xfoil v6.99) to produce a comparative study between several airfoils that have been selected for their use in low-Re research, along with a wing sizing study to determine appropriate wing area and velocities to maintain steady level flight in the Martian Atmosphere. Results have indicated one of the best suited airfoil for this vehicle is the SD7003 airfoil, selected for its exemplary low Re efficiency and steady/gradual stall behaviour. Traveling at 40m/s using the SD7003 airfoil, the vehicle would require wings of approximately 1.25m in length and 0.4m in chord length. The vehicle would be powered by an electrically driven counter rotating co-axial pair of propellers and will be controlled aerodynamically using control surfaces during flight, and during VTOL manoeuvres it would be controlled by gimbling the propellers. The study concludes that a 5kg MAEVE concept is technically feasible and capable of producing valuable data for the future generations of planetary aerial exploration.​
Keywords: Airfoil; Air Density; Mars; fixed wing; Validation; Viscosity